Seroprevalencia y factores asociados a fiebre Q en cerdos en el cantón Loja, Ecuador - Esparza Montaño, Josselyn Alejandra (2024)
In the present study, the seroprevalence of Q fever in pigs in Loja Canton was investigated, with a seroprevalence of 2.14%. The main objective was to determine both the prevalence of infection and the risk factors associated with it. To achieve this, several factors were explored, including the total production area, the presence of fattening sheds, the origin of the animals (through purchase), the destination of pig carcasses, feeding with harvest by-products and kitchen waste, age at weaning less than 30 days, the application of clostridial vaccines and the presence of specific health conditions such as high mortality of adults and piglets, abortions, diarrhea, and practices such as dehorning and dehive. On the other hand, the risk factors identified were: total production area, feedlot management, animal purchase (origin), the destination of pig carcasses, age at weaning, the presence of abortions and the handling of anticlostridial vaccines, all of which can play a significant role in the spread of Coxiella burnetii. These factors highlight the importance of biosecurity and proper management practices in the swine industry to minimize transmission of infection. In summary, this study contributes to the understanding of the prevalence of Q fever in pigs in Canton Loja, Ecuador, and provides a detailed evaluation of the factors that contribute to the spread of infection. In summary, this study contributes to the understanding of the prevalence of Q fever in pigs in Cantón Loja, Ecuador, and provides a detailed assessment of the related risk factors. These results can serve as a basis for future infection control and prevention strategies, both in terms of animal and human health. Cooperation between the public health and swine industry sectors is essential to effectively address the Q fever problem in the region.